2022
DOI: 10.3389/fcell.2022.981893
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of the bZIP transcription factors Mafg and Mafk causes misexpression of genes in distinct pathways and results in lens embryonic developmental defects

Abstract: Deficiency of the small Maf proteins Mafg and Mafk cause multiple defects, namely, progressive neuronal degeneration, cataract, thrombocytopenia and mid-gestational/perinatal lethality. Previous data shows Mafg−/−:Mafk+/- compound knockout (KO) mice exhibit cataracts age 4-months onward. Strikingly, Mafg−/−:Mafk−/− double KO mice develop lens defects significantly early in life, during embryogenesis, but the pathobiology of these defects is unknown, and is addressed here. At embryonic day (E)16.5, the epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 87 publications
1
9
0
Order By: Relevance
“…This unexpected result was our first clue about compensatory upregulation or deregulation in KO animals. In addition to our data, a recent work described marked downregulation of Epha5 transcripts in developing lenses with the disruption of the musculoaponeurotic fibrosarcoma ( MAF ) family of proteins [ 44 ]. The data from RNA-seq plates did not distinguish between the 14 variants of Epha5 .…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This unexpected result was our first clue about compensatory upregulation or deregulation in KO animals. In addition to our data, a recent work described marked downregulation of Epha5 transcripts in developing lenses with the disruption of the musculoaponeurotic fibrosarcoma ( MAF ) family of proteins [ 44 ]. The data from RNA-seq plates did not distinguish between the 14 variants of Epha5 .…”
Section: Discussionsupporting
confidence: 70%
“…The data from RNA-seq plates did not distinguish between the 14 variants of Epha5 . MAFs encode basic leucine zipper transcription factors that are known to be important for lens development and to be involved cataractogenesis [ 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. There may be other insights that can be gleaned from the microarray data between the control, EphA2 −/− , and ephrin-A5 −/− lens samples.…”
Section: Discussionmentioning
confidence: 99%
“…For the full result of the motif analysis, see Additional file 9 . Importantly, previous studies have shown major roles of c-Maf [ 99 101 ], Hif1α [ 102 104 ], MafG and MafK [ 105 , 106 ], and RAR/RXR [ 107 109 ] in control of lens-specific transcription. The NF1 and TEAD motifs were also previously identified using open chromatin analysis [ 44 ]; nevertheless, no data are available for individual transcription factors recognizing these motifs from previous lens studies.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the 2019 study by Zhao et al in E14.5 and P0.5 mice identified FOXO3, several Maf family members (Mafa, Mafg, Mafk), CTCF, Pax6, Hsf4, and Sox1 as the predicted factors ( Table 3 ). The transcription factors Pax6 [ 46 , 144 , 145 ], Hsf4 [ 55 , 56 , 57 ], Sox1 [ 161 ], and Mafg/Mafk [ 72 , 73 ] have established functions while others have functions that have yet to be investigated in the lens. Pax6 is expressed in the anterior pre-placodal region that gives rise to the adenohypophyseal, olfactory, and lens placodes [ 162 ].…”
Section: Analysis Of Chromatin Landscape In Lens Tissues With Atac-seqmentioning
confidence: 99%